Prinsip Keadilan dalam Perlindungan Hukum Dokter Kandungan Atas Gugatan Malpraktik Berdasarkan UU No. 17 Tahun 2023 - Elsy Nur Anggraeni; Rini Irianti Sundari; Hadi Susiarno; Aslan Noor (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Obstetricians are often confronted with medical malpractice lawsuits, even when they have acted in accordance with professional standards, medical service standards, operational procedures, and medical ethics. Medical malpractice is generally defined as negligence or deviation from professional standards that results in serious harm to patients (Fiscina, 1999). This study aims to examine the application of the concept of medical malpractice along with its legal implications and to analyze the forms of legal protection available to obstetricians under Law Number 17 of 2023 on Health, viewed from the perspective of the principle of justice. Using a normative juridical method with descriptive-analytical specifications, the research employed a literature study and qualitative deductive analysis. The results indicate that legal protection for obstetricians consists of two dimensions: preventive and repressive. Preventive protection includes the implementation of informed consent, proper medical records, and compliance with standard operating procedures. Repressive protection involves legal defense mechanisms and institutional or professional organizational support. However, this protection remains suboptimal, as the decisions of the Indonesian Medical Disciplinary Board (MKDKI) are not always taken into account by the courts (Rahman, 2022). From the perspective of Rawls’ principle of justice, protection for obstetricians should ensure a balanced recognition of both patients’ and doctors’ rights, thereby promoting fairness and equitable justice for all parties (Rawls, 1971).